Mono- and binuclear palladacycles via regioselective C-H bond activation: syntheses, mechanistic insights and catalytic activity in direct arylation of azoles - Pandey, Dilip K.; Khake, Shrikant M.; Gonnade, Rajesh G.; Punji, Benudhar (RSC Advances, 2015)
{Regioselective C-H bond palladation of the hybrid pincer-type ligands, 3-R2PO-C6H4-1-(CH2NPr2)-Pr-i [(POCNiPr2)-P-R2-H; R = Ph (1a)